Pengaruh Penambahan Kardus Dan Air Leri Terhadap Produktivitas Jamur Merang (Volvariella volvaceae) Yang Ditanam Pada BAGLOG - Murti, Pramita Restu; , Dra. Suparti, M.Si (2015)
Cardboard is processed from wood that has the main content in the form of cellulose, so the cardboard is expected to be used as a planting medium mushroom. Leri water contains minerals, vitamins B1, B12, and nutrients that can be utilized as additional nutrients for the growth of mushroom. The purpose of this study was to determine the effect of cardboard and water leri on the productivity of mushroom grown on baglog. This study was prepared by completely randomized design (CRD) with two factors and three replications. Factor 1 heavy cardboard (P1) 125 grams, (P2) 250 grams, (P3) 375 grams. Factor 2 leri volume (L1) and 50 ml (L2) of 100 ml. Parameters measured were body weight of the fruit and the number of mushroom fruit body. Data were tested by analysis of variance 2 lanes. Based on the analysis of variance showed that the addition of cardboard and water leri media with different concentrations of influence on the body weight of the fruit and the number of mushroom fruit body. The best treatment for the body weight of the fruit is P3L1 namely 79.16 grams, while the lowest was P0L1 treatment is 56.67 grams. The best treatment for a number of fruiting bodies is P3L1 is 6 pieces, while the lowest treatment P0L0 ie 4 pieces.